The SOY MARKET IN BRAZIL POST-COVID-19 PANDEMIC - Biscaia, Welington Fernando; Bertaci, Moacir José (Revista Interface Tecnológica, 2022)
Agriculture in Brazil is very strong, and the country is a major food exporter. The country is one of the largest grain exporters in the country, among which soybean stands out, used especially for the manufacture of oil and animal feed. At the beginning of 2020, the world experienced the SARS-CoV-2 coronavirus pandemic, which in a short time reached all countries. China, the stage for the onset of the disease, is the largest importer of soybeans from Brazil, a factor that has had an impact on the market in general, but especially for this crop. The objective of this study is to highlight the Brazilian soy market in the context of the pandemic. The methodology used was a literature review with consultations in articles and websites that bring the topic in a serious and well-founded way. The results point out that the soy market, as well as the agricultural sector in a broad way, suffered impacts and seek to face the mitigation of the pandemic, seek recovery.
Keywords: Soy; Marketplace; Pandemic; COVID-19